Analisis Makna Karya Sastra Puisi Pada Buku Surat Dari Samudra Antologi Puisi Anak Pada Pembelajaran Sekolah Dasar - Yunianto, Teguh; Muhammad Singgih (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2024)
Abstract The problem raised is related to the meaning of literary works of poetry in the book Letters from Ocean, an anthology of children's poetry. Poetry is one of the appropriate pieces of literature to describe the writer's thoughts, both regarding the social life of society and its various gaps, as well as as a medium for conveying criticism to individuals and groups. The aim of this research is to ensure that the literary work produced does not deviate from things that endanger the author's existence. The method used in this research is a qualitative method. The data analysis technique that the author uses in this research is: 1) Read the poem carefully several times. 2) then write the meaning in the poem. 3) Mark sentences that contain meaning in the poem. 4) Analyze the meaning based on the data obtained. The meaning of the literary works of poetry contained in the book Letters from Ocean, an anthology of children's poetry entitled Selendang Batik Ibu, My Teacher, Father and Mother, Wind, Going to School and Lazy, contains the meaning of poetry literary works which include the sacrifice of a mother, a teacher like the shining sun, love. parents to their children, wind that is beneficial but can be a disaster, motivating children to be enthusiastic and diligent in studying, and feeling lazy about not having a goal to achieve their goals. Keywords: literary works, anthologies, ocean letter books Abstrak Permasalahan yang diangkat berkaitan dengan makna karya sastra puisi pada buku surat dari samudra antologi puisi anak. Puisi salah satu sastra yang tepat untuk menggambarkan pikiran penulisnya, baik menyangkut tentang kehidupan sosial masyarakat dengan berbagai kesenjangannya, maupun sebagai salah satu media untuk menyampaikan kritik kepada perorangan maupun golongan. Tujuan penelitian ini Agar karya sastra yang dihasilkan tidak menyimpang dari hal-hal yang membahayakan eksistensi pengarang. Metode yang digunakan dalam penelitian ini ialah metode kualitatif. Teknik analisis data yang penulis gunakan dalam penelitian ini adalah: 1) Membaca puisi dengan berulangkali dengan seksama. 2) kemudian menulis makna yang ada didalam puisi tersebut . 3) Menandai kalimat-kalimat yang mengandung makna dalam puisi tersebut. 4) Menganalisis makna berdasarkan data yang didapat. Makna karya sastra puisi yang terdapat pada buku surat dari samudra antologi puisi anak yang berjudul Selendang Batik Ibu, Guruku, Ayah dan Ibu, Angin, Berangkat Sekolah dan Malas mengandung makna karya sastra puisi yang diantaranya pengorbanan seorang ibu, guru seperti Mentari bersinar, kasih sayang kedua orangtua kepada anaknya, angin yang bermanfaat namun dapat menjadi bencana, motivasi anak agar semangat dan rajin menimba ilmu, dan rasa malas tidak memiliki tujuan menggapai cita-cita Kata Kunci: karya sastra, antologi, buku surat Samudra